TYPOLOGY AND STAGES OF THE TEACHING EXERCISE - PANICO, Vasile PANICO; ȚURCAN, Violeta (Acta et Commentationes, Sciences of Education, 2019)
The study is devoted to the analysis and development of concept exercise. This paper reflects the grounds/scientific criteria typology of exercises: components of personality structure, types of social activities, educational objectives, components of social culture reflected in the content of education, stages of educational material properties, the paper describes and characterizes the stages/phases of the exercise.